Undifferentiated Sarcoma as Intermediate Step in Rhabdomyosarcomatous Transformation of a Metastatic Malignant Melanoma Resistant to Anti-BRAF Therapy: A Phenomenon Associated With Significant Diagnostic and Therapeutic Pitfalls. (September 2019) - Tran, Tien Anh N.
Undifferentiated sarcoma has been hypothesized as an intermediate step in the progression of malignant melanoma to rhabdomyosarcoma. The current report describes a new case of rhabdomyosarcomatous transformation in a malignant melanoma and documents the temporal progression of the malignant melanoma to rhabdomyosarcoma in different metastatic sites via undifferentiated sarcoma. A 65-year-old female with a past medical history of malignant melanoma presented with a new lung mass. A core biopsy revealed a malignant spindle cell neoplasm that was negative for all melanocytic markers, suggesting the possibility of a primary pulmonary sarcomatoid carcinoma or sarcoma. The subsequent lobectomy demonstrated an undifferentiated spindle cell neoplasm with areas of rhabdomyoblastic differentiation. Review of the skin lesion and lymph nodes confirmed the diagnosis of the primary cutaneous malignant melanoma, but also revealed that the nodal metastases had largely transformed into an undifferentiated sarcoma with similar morphology as the spindle cell neoplasm in the lung. Molecular studies demonstrated an identical BRAF V600E mutation in both the primary malignant melanoma and the lung tumor. Interestingly, the metastatic malignant melanoma with rhabdomyosarcomatous transformation was the single metastasis resistant to anti-BRAF therapy, whereas other metastases displayed dramatic clinical responses. The case report provides further supportive evidence that undifferentiated sarcoma is an intermediate step in the progression of malignant melanoma to rhabdomyosarcoma. Pathologists should be aware of this phenomenon as proper documentation of an undifferentiated sarcoma or newly acquired phenotypic variations in a malignant melanoma could considerably improve diagnostic accuracy and therapeutic management of subsequent recurrences.